Analytic method for solitary solutions of some partial differential equations - Ugurlu, Yavuz; Kaya, Dogan (Elsevier Science Bv, 2007)
In this Letter by considering an improved tanh function method, we found some exact solutions of the clannish random walker's parabolic equation, the modified Korteweg-de Vries (KdV) equation, and the Sharma-Tasso-Olver (STO) equation with its fission and fusion, the Jaulent-Miodek equation. (C) 2007 Elsevier B.V All rights reserved.
Keywords: improved tanh function method; KdV equation; Soliton solution; Clannish random walker's parabolic equation; STO equation with its fission and fusion; Jaulent-Miodek equation